Reduction of income inequality and subjective well-being in Europe - Tamás Hajdu; Gábor Hajdu (Kiel Institute for the World Economy (IfW), 2014)
Using four waves of the European Social Survey (179,273 individuals from 29 countries) the authors analyze the association of reduction of income inequality (redistribution) with subjective wellbeing. Their results provide evidence that people in Europe are negatively affected by income inequality, whereas reduction of inequality has a positive effect on well-being. Since the authors simultaneously estimate the effects of income inequality and its reduction, their results indicate that not only the outcome (inequality), but also the procedure (redistribution) that leads to the outcome influences subjective well-being. The authors argue that living in a country where taxes and transfers reduce income inequality to a greater extent, the poor may feel more protected, and the rich may also feel more generous, which may result in an emotional benefit for them. It is also possible that well-being is associated not only with actual, but also with perceived inequality. The positive effect of redistribution seems to be stronger for less affluent members of the societies and left-wing oriented individuals. The estimations are different in Eastern and Western Europe: In post-communist countries people appear to be harder hit by inequality, whereas the impact of inequality reduction on well-being is higher in the East than in the West.
Keywords: D63; I31; 330; subjective well-being; satisfaction; inequality; redistribution; inequality reduction